Prawda i pozór w „Munimatalankarze" („Munimatālaṁkāra”) Abhajakaragupty (Abhayākaragupta) - Glinicka , Małgorzta (Hybris, 2014)
This is a selected translation drawn from Munimatālaṁkāra (The Ornament of the Sage’s Intention), authored by Abhayākaragupta (c. 1100), one of the last great masters of Buddhism in India. He wrote on most major areas of Buddhist practice and thought (Mahāyāna doctrine and the path, Tantric ritual and meditation).The text does not appear to survive in the original sanskrit. It was translated by the author’s Tibetan disciple Dpang-zho Gsal-ba-grags in Nalanda.=, and later revised by Dpang Lo-tsā-ba Blo-gros-brtan-pa (1276–1342).The passage chosen here is drawn from the final section of the lengthy first chapter of Munimatālaṁkāra, entitled the “appearance of the enlightened mind”. The chapter traces the course of the path from the initial cultivation of the aspiration to enlightenment through to the development of discernment, or wisdom. The analysis of the two truths is introduced in this context.